AXIOLOGICAL DIMENSIONS OF YOUTH ENGAGEMENT WITH HISTORICAL CONSCIOUSNESS AND MORAL VALUES: A PHILOSOPHICAL ANALYSIS - Dilnoza Adhamjonkizi Tursunova, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. This article examines the axiological dimensions of youth engagement with historical consciousness and moral values from a philosophical perspective. Historical consciousness and moral values are analyzed as interrelated components that shape young people’s worldview, ethical orientation, and social responsibility. The study emphasizes that historical consciousness is not merely knowledge of the past but a value-based interpretation of historical experience. In the context of globalization and cultural pluralism, the article explores the challenges faced by youth in maintaining stable moral orientations. It argues that an axiological approach provides a theoretical foundation for strengthening youth engagement with historical heritage and moral values, thereby contributing to moral continuity and sustainable social development.